Pengaruh Lingkungan Kerja Dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Karyawan Yang Dimediasi Oleh Keyakinan Diri - Hidayat, Daffa; Nurdin, Ridwan (Manajemen Inovasi Bisnis dan Strategi, 2024)
This study aims to examine the influence of the Work Environment and Leadership Style on Job Satisfaction which is mediated by Self-Confidence in the Pidie Public Works and Spatial Planning Department. The sample used was 133 respondents. Data was collected using a questionnaire. The data analysis technique used is the Multiple Linear Analysis Method using Statistical Package For Social Science (SPSS) software. The results of this analysis show that the Work Environment and Leadership Style have a significant effect on Job Satisfaction at the Pidie Public Works and Spatial Planning Department. Meanwhile, Self-Confidence mediates the influence of the Work Environment and Leadership Style on Job Satisfaction.Keywords: Work Environment; Leadership Style; Self-Confidence; Job Satisfaction